PENGARUH PROFITABILITAS, LEVERAGE, KEBIJKAN DIVIDEN, UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN CONSUMER GOODS INDUSTRY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Putri Andriani; Yolandafitri Zulvia (JAMER : Jurnal Akuntansi Merdeka, 2025)
This study aims to analyze the influence of (1) profitability on company value, (2) leverage on company value, (3) dividend policy on company value, (4) company size on the value of consumer goods industry companies listed on the Indonesia Stock Exchange in 2017-2021. The population in this study is consumer goods industry sector companies listed on the Indonesia Stock Exchange. Meanwhile, the sample in this study was determined by the purposive sampling method, namely consumer goods industry companies for five consecutive years from 2017-2021 so that a sample of 15 companies with 75 observation data was obtained. The analysis method used is the multiple linear regression method using the IBM SPSS Statistics 25 program. The results of this study conclude that (1) profitability has a positive and significant effect on the company's value, (2) leverage has no effect on the company's value, (3) dividend policy has no effect on the company's value, (4) the size of the company has a positive and significant effect on the company's value.